2006
DOI: 10.1124/jpet.106.111526
|View full text |Cite
|
Sign up to set email alerts
|

Desoxyrhaponticin (3,5-Dihydroxy-4′-methoxystilbene 3-O-β-d-glucoside) Inhibits Glucose Uptake in the Intestine and Kidney: In Vitro and in Vivo Studies

Abstract: Rhubarb extracts have been reported to improve oral glucose tolerance in diabetic animals. In the present study we have investigated the antidiabetic actions of desoxyrhaponticin, a major stilbene in rhubarb, as a glucose uptake inhibitor. Desoxyrhaponticin was demonstrated to inhibit glucose uptake in rabbit intestinal membrane vesicles as well as in rat everted gut sleeves, with IC 50 values of 148.3 and 30.9 M, respectively. Kinetics studies revealed that desoxyrhaponticin is a competitive inhibitor of gluc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 40 publications
1
10
0
Order By: Relevance
“…The glucose transporter isoforms GLUT4 and GLUT1 are highly expressed in muscle cells, with GLUT4 being more abundant in an intracellular compartment from which it is quickly translocated to the plasma membrane as a response to insulin challenge. Both insulin-dependent and non-insulin-dependent diabetes were shown to reduce glucose utilization in muscle either due to a defective expression or dysregulation in GLUT4 translocation [3], [18]. In the present study, glucose uptake was found to be normal in the control group treated with no insulin.…”
Section: Resultssupporting
confidence: 41%
See 1 more Smart Citation
“…The glucose transporter isoforms GLUT4 and GLUT1 are highly expressed in muscle cells, with GLUT4 being more abundant in an intracellular compartment from which it is quickly translocated to the plasma membrane as a response to insulin challenge. Both insulin-dependent and non-insulin-dependent diabetes were shown to reduce glucose utilization in muscle either due to a defective expression or dysregulation in GLUT4 translocation [3], [18]. In the present study, glucose uptake was found to be normal in the control group treated with no insulin.…”
Section: Resultssupporting
confidence: 41%
“…Given the increased perception that handling the early stages of diabetes is of crucial importance, several recent studies and approaches are focusing on agents that can delay or inhibit glucose absorption. Delaying glucose absorption, such as by blocking glycoside hydrolases (particularly α-glucosidases), allows extended time for β-cells to increase insulin secretion, and thereby reduce circulatory glucose levels [3], [4].…”
Section: Introductionmentioning
confidence: 99%
“…Polyhydroxystilbenes (PHS) are believed to occur commonly in many unofficial Da‐huang species and have raised increasing attention due to their anti‐tumour (Jang et al , ; Lee et al , ), anti‐diabetic (Li et al , ), coronary heart protecting (Renaud and de Lorgeril, ), anti‐hyperlipidemic (Matsuda et al , ), liver damage reducing (Raal et al , ) and anti‐adipositas (Tran et al , ) effects, as well as other potential bioactivities (Tadashi et al , ). Hence, the requirement of high‐purity PHS for pharmacological and clinical trials has increased the interest in their preparation.…”
Section: Introductionmentioning
confidence: 99%
“…Type II diabetes has become a major health problem in both developed and developing countries (Li et al, 2006). The problem shows an increasing incidence in aboriginal populations, such as the Cree of Eeyou Istchee (CEI-James Bay area of Northern Quebec, Canada), probably due to a genetic predisposition (Zimmet et al, 1997) and to environmental factors like excessive energy intake and physical inactivity (Campbell et al, 1994).…”
Section: Introductionmentioning
confidence: 99%